Le descrizioni della performance: esperienze dell'oralità e pratica di scrittura nella Ferrara rinascimentale - Giuseppe Lipani (Annali Online dell'Università di Ferrara. Sezione Lettere)
In a description of a Renaissance performance, writing transfigures the actual experience of the public, making ambiguous the testimonial value of the source itself. Starting from some examples concerning Ferrara’s stage, this paper discusses some methodological issues in approaching these sources.